(untitled) (Global Journal of Management and Business Research, 2018)
IDCOL: Problems and Prospects-Before throwing light on the research work, the researcher feels it proper to provide a brief overview of Industrial Development Corporation of Odisha Limited (IDCOL). Industrial Development Corporation of Odisha Limited (IDCOL) was established by the government of Odisha in the year 1969 with a mission to promote industries in the state of Odisha, which is poor, in spite of its mineral wealth. The objective of the establishment of IDCOL was to overcome the entrepreneurial deficiency in the state by setting up medium scale industries in Odisha, with a hope that the industrial growth will contribute to economic growth of the state, which is essential for addressing the spiralling poverty of the state. The vision was clearly demonstrated by the state government which preferred to keep pace with the rapid industrialisation in the country and for that matter, in the world. With an authorised capital of Rs. 50 crores, Industrial Development Corporation of Odisha Limited (IDCOL) started functioning and subsequently, Hirakud Industrial Work, Kalinga Iron Works, Ferrochrome Plant, Hira Cement Works, Hira Cables, Re-Rolling Mill, Boiler Piping and Accessories Works, Orichem Ltd., East Coast Breweries and Distilleries Ltd., ABC Spinning Odisha Ltd., Konark Jute Limited, NICCO Industries Ltd., SN Corporation Ltd. And other subsidiary units were established, which produced fabrication of transmission line towers, pig iron and cast iron, high carbon and low carbon ferrochrome, Portland cement, AAC and ACSR conductors, M.S. rods, fabrication of piping bend, Sod. Sulphate, beer, fine cotton and synthetic yarn, heavy cess cement bags, PVC cables, high tensile fasteners and other products respectively